Temperature and Cr-Co ratio on Production of Diethyl Ether from Ethanol Dehydration using Cr-Co/γ-Al2O3 Catalyst - Muna, Izza Aliyatul; Kurniawansyah, Firman; Mahfud, Mahfud; Roesyadi, Achmad (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
The running down of fossil fuels and rising environmental concerns, there is an increasing emphasis on identifying eco-friendly alternative energy sources. Diethyl ether (DEE) is considered one such additive fuel that can replace fossil fuels. In this study, DEE was synthesized through the reaction dehydration of ethanol using γ-alumina catalysts impregnated with chromium and cobalt. The dehydration of ethanol performed in a fixed bed reactor using Cr-Co/γ-Al2O3catalysts loading. The effect of metal ratio of Cr-Co was examined. Catalyst characterization was carried out using XRD, BET, and SEM-EDX analyses. The dehydration reaction was conducted in a fixed-bed reactor at temperatures 100 to 200 ºC, with nitrogen gas flowrates between 200 and 600 mL/min as the carrier gas. The findings revealed that the increase chromium contents, and the temperature were augmenting the diethyl ether yield. And the increase of nitrogen flow rate is slightly increasing the yield of DEE and conversion of ethanol. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).